Association between mct1 gene polymorphism (rs1049434) with the athletic performance of elite track and field athletes - ULUCAN, KORKUT (My University, 2023)
Abstract:Monocarboxylate transporter 1 (MCT1; SLC16A1) is a proton-dependent cotransporter/exchanger, located on the apical membrane of cells. MCT1 is able to transport several monocarboxylates including lactate, pyruvate and acetate, which makes this protein critical in terms of the athletic performances. The rs1049434 polymorphism in theMCT1gene was frequently associated with the performance of the athletes in different populations. The present study aims to decipher any possible association of the rs1049434 polymorphism with the personal best of elite track and field athletes. A total of sixty elite athletes (31 sprint/power and 29 endurance) and twenty control/sedentary with the ages of 18-35 voluntarily participated in the study. The International Association of Athletics Federations (IAAF) score scale was used to determine the performance levels of the personal best (PB) of the athletes. Whole exome sequencing (WES) was performed by the genomic DNA isolated from blood of the participants. Sport type, sex and PB were chosen as the parameters to compare within and between the groups by logistic regression models. The sex was not the criterion that was significantly different between or within the groups. Although PB scores were not significant within the sprint/power group, it was significant within the endurance group by the codominant (p=0.044), dominant (p=0.016) and over-dominant (p=0.048) models. The rs1049434 polymorphism in theMCT1gene may be linked to the PB of the endurance athletes. However, other genetic alterations should be regarded to conclude the effect of this polymorphism. The multi-factorial genetic background that could associate with the athletic performanceis still under investigation in our research group. Nevertheless, further studies with more participants are needed.

Monokarboksilat transporter 1 (MCT1; SLC16A1), hücrelerin apikal membranında lokalize olan bir proton bağımlı birlikte taşıyıcıdır/değiştiricidir. MCT1 laktat, pirüvat ve asetat gibi monokarboksilatların transportunda görev alır ve bu durum bu proteini atletik performans açısından önemli kılar. MCT1 genindeki rs1049434 polimorfizmi, farklı popülasyonlarda atletlerin performansı ile sıkça ilişkilendirilmiştir. Sunulan çalışma, Türk popülasyonunda, elit atletlerde, atletik performans ile rs1049434 polimorfizmi arasındaki olası ilişkiyi açığa çıkartmayı amaçlamaktadır. Çalışmaya, yaşları 18-35 arası değişen ve 31 sprint/güç ve 29 dayanıklılık olmak üzere altmış elit atlet ve yirmi kontrol dahil edilmiştir. Atletlerin performans seviyeleri, kişisel en iyi dereceleri (PB) aracılığıyla Uluslararası Atletizm Federasyonu (IAAF) skor ölçeğine göre belirlenmiştir. Katılımcılardan elde edilen periferik kandan izole edilen DNA’dan tüm ekzom dizileme (WES) çalışılmıştır. Spor türü, cinsiyet ve PB, doğrusal regresyon modelleriyle gruplar içinde ve arasında analiz edilmiştir. Cinsiyet, gruplar içinde ve arasında istatistiksel olarak anlamlı bir fark tespit edilmemiştir. Sprint/güç grubunda PB anlamlı olmasa da dayanıklılık grubunda kodominant (p=0.044), dominant (p=0.016) ve over-dominant (p=0.048) modelleri ile anlamlı sonuçlar olduğu saptanmıştır. MCT1 genindeki rs1049434 polimorfizmi, dayanıklılık sınıfındaki atletlerin PB düzeyleriyle ilişkili olabilir. Ancak, diğer olası genetik faktörler dikkate alınmalıdır. Atletik performansı etkileyebilecek multifaktöriyel genetik arkaplan grubumuzca devam ettirilen çalışmalar arasındadır. Yine de daha fazla katılımcı ile ileri çalışmalara ihtiyaç duyulmaktadır.
Elit atletlerde mct1 gen polimorfizminin (rs1049434) atletik performans ile ilişkisinin araştırılması
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Atletizm; sporcu; koşucu; rs1049434; polimorfizm; MCT1; SLC16A1; Athletics; athlete; runner; polymorphism